SEA TUTOR: INKUBATOR TELUR PENYU UPAYA KONSERVASI PENYU DI PULAU NIAS - Astrid Fauzia Dewinta; Vindy Rilani Manurung; M. Azis Rizky Lubis; Aura Muhshi Sam Siregar; Firman Saidu Kandias; Deka Bagas Setiawan (Jurnal Abdi Insani, 2026)
Nias Island is one of the sea turtle nesting sites in Indonesia facing the threat of extinction due to human activities and environmental changes. The success rate of conventional sea turtle egg hatching is still low, only 50%, thus technological innovation is needed to improve conservation success. More effective sea turtle egg incubation is a primary need to support the preservation of this species. The objective of this activity is to increase the success rate of sea turtle egg hatching through the implementation of Sea Turtle Incubator technology with an automatic control system and the empowerment of the local community. The method includes problem identification, design of a microcontroller-based incubator with temperature and humidity sensors, prototype implementation at the Nias Turtle Conservation House for 3 months (August 1, 2025 – October 31, 2025), technical training for the community, and monitoring of hatch results during this period. The results showed that the use of the Sea Turtle Incubator in 2 incubation tanks with 50 eggs each increased the hatching rate to 80–100%, compared to the conventional method which only reached about 50% per incubation tank. The average hatching percentage of the automatic incubator reached 80–100%, while the traditional method averaged 50%. Additionally, the training improved community knowledge and formed new conservation groups, opening opportunities for conservation ecotourism. In conclusion, Sea Turtle Incubator technology effectively increases the success of sea turtle egg hatching and can strengthen community roles in sustainable conservation on Nias Island.